2011
DOI: 10.1021/es2005557
|View full text |Cite
|
Sign up to set email alerts
|

Biotransformation of Nitrosamines and Precursor Secondary Amines under Methanogenic Conditions

Abstract: b S Supporting Information ' INTRODUCTION Nitrosamines (NISA) are an emerging group of disinfection byproducts and suspected carcinogens. 1 Among all nitrosamines, N-nitrosodimethylamine (NDMA), N-nitrosomethylethylamine (NMEA), N-nitrosopyrrolidine (NPYR), N-nitrosodiethylamine (NDEA), N-nitrosodi-N-propylamine (NDPA), and N-nitrosodi-N-butylamine (NDBA), are of particular interest because they are listed in the Unregulated Contaminant Monitoring Regulation (UCMR 2) 2 as well as the recently proposed Contamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…Removal ratios ranged from 38.1% to 85.4%, listed here in decreasing order: NDMA (85.4%), NDPA (78.8%), NDEA (47.7%), Npyr (48.5%), and NDBA (38.1%). In previous studies, many isolates belonging to different genera have shown a biodegradation capacity for NDMA at high concentrations, and propane monooxygenases (PrMO), soluble methane monooxygenases (sMMO) and toluene monooxygenases (TMO) enhanced the biodegradation of NDMA as the nitrogen source (Fournier et al, 2006(Fournier et al, , 2009Sharp et al, 2005Sharp et al, , 2007Sharp et al, , 2010Tezel et al, 2011). When cultures were grown on media with added organics (i.e., propane, methane or toluene) as the carbon source, the degradation rates increased.…”
Section: Biodegradation Of Nitrosamines By the Isolated Bacteriummentioning
confidence: 99%
See 4 more Smart Citations
“…Removal ratios ranged from 38.1% to 85.4%, listed here in decreasing order: NDMA (85.4%), NDPA (78.8%), NDEA (47.7%), Npyr (48.5%), and NDBA (38.1%). In previous studies, many isolates belonging to different genera have shown a biodegradation capacity for NDMA at high concentrations, and propane monooxygenases (PrMO), soluble methane monooxygenases (sMMO) and toluene monooxygenases (TMO) enhanced the biodegradation of NDMA as the nitrogen source (Fournier et al, 2006(Fournier et al, , 2009Sharp et al, 2005Sharp et al, , 2007Sharp et al, , 2010Tezel et al, 2011). When cultures were grown on media with added organics (i.e., propane, methane or toluene) as the carbon source, the degradation rates increased.…”
Section: Biodegradation Of Nitrosamines By the Isolated Bacteriummentioning
confidence: 99%
“…When cultures were grown on media with added organics (i.e., propane, methane or toluene) as the carbon source, the degradation rates increased. In addition to the biodegradation of NDMA, a few reports (Carissa and Jonathan, 2013;Tezel et al, 2011) focused on the biotransformation of other nitrosamines. Multiple nitrosamines at high concentrations have been biodegraded as the nitrogen source by an isolate reported by Carissa and Jonathan (2013), growth of cells on propane as the sole carbon source greatly enhanced degradation rates.…”
Section: Biodegradation Of Nitrosamines By the Isolated Bacteriummentioning
confidence: 99%
See 3 more Smart Citations